'Fragmentation' of NMJs: a sign of degeneration or regeneration? A long journey with many junctions. (15th July 2020) - Slater, Clarke R.
Abstract: Mammalian neuromuscular junctions (NMJs) often consist of curved bands of synaptic contact, about 3–6 μm wide, which resemble pretzels. This contrasts with the NMJs of most animal species which consist of a cluster of separate synaptic spots, each of which is also about 3–6 μm across. In a number of situations, including a variety of disease states as well as normal ageing, mammalian NMJs acquire a more 'fragmented' appearance that resembles somewhat that of other species. This 'fragmentation' of the NMJ has sometimes been interpreted as a 'disintegration' or 'degeneration', with the suggestion that it might be associated with impaired neuromuscular transmission. An alternative view is that NMJ fragmentation is the outcome of a normal process by which the NMJ is maintained in an effective state. In this highly personal commentary, I cite a number of examples of this and point out that although the 'pretzel' form arises during normal development as a result of the sculpting of an immature synaptic 'plaque', in virtually all situations where new synaptic contact is established in adult mammals this occurs by the addition of new synaptic 'spots' rather than by the extension, or neoformation, of 'pretzels'. Further, where appropriate studies have been performed, no evidence of a correlation between the degree of fragmentation and the efficacy of transmission has emerged. It may therefore be more appropriate to consider NMJ 'fragmentation' as a form of regeneration, rather than of degeneration. This article is part of a Special Issue entitled: Honoring Ricardo Miledi - outstanding neuroscientist of XX-XXI centuries . Highlights: Mammalian neuromuscular junctions (NMJs) often consist of curved bands of synaptic contact which resemble pretzels. In ageing and disease NMJs are often transformed into a set of discrete spots of synaptic contact similar to the NMJs in most non-mammalian animals. One view is that this 'fragmentation' reflects a degenerative process likely to be associated with impaired neuromuscular transmission. However, functional spot-like synaptic contacts often form in adult mammals when the motor nerve terminal responds to a challenging environment. I suggest that NMJ 'fragmentation' reflects the remarkable regenerative capacity of NMJs rather than the results of a process of degeneration.